Origin of carbonate cements and reservoir evolution of tight sandstone in the Upper Triassic Yanchang Formation, Ordos Basin, China. Issue 8 (17th November 2019) - Mao, S. W.; Bao, Z. D.; Wang, X. X.; Gao, Y. S.; Song, J.; Wang, Z. C.; Liu, W.; Zhang, L.; Wei, M. Y.; Bao, Y. F.
Abstract: The Upper Triassic Chang 8 Member, the eighth member of the Yanchang Formation, is a key reservoir interval in the Jiyuan area of the Ordos Basin. The reservoir quality of the Chang 8 Member tight sandstones is extremely heterogeneous owing to the widespread distribution of carbonate cements. The carbonate cements commonly develop near sandstone–mudstone interfaces and gradually decrease away from the interfaces to the centres of the sand bodies. However, the content of carbonate cements (≤6%) has a positive correlation with the visual porosity in the Chang 8 Member sandstone, revealing that the carbonate cements contribute to the compaction resistance and the residual primary pores of reservoirs during the diagenetic process. Three main types of carbonate cement are identified: type I (calcite), type II (calcite and ferrocalcite), and type III (dolomite and ankerite). The type I calcite is characterised by enriched δ 13 C (mean –3.41‰) and δ 18 O (mean –15.17‰) values compared with the type II (mean δ 13 C = –7.33‰, δ 18 O = –18.90‰) and type III (mean δ 13 C = –10.0‰, δ 18 O = –20.2‰) cements. Furthermore, the mean δ 18 O value (–4.7‰) of the type I pore fluids is 1.5‰ and 0.9‰ lower than the type II (mean –3.2‰) and type III (mean –3.8‰) pore fluids, respectively. This indicates that the evolving pore fluids experienced some relative strong water–rock interactions that provided the original materials (e.g. Ca 2+, Fe 3+, and Mg 2+ ) for the carbonate cements during the diagenetic process. The highly saline lake water directly provided the primary material for the type I calcite precipitation, which also provided the material necessary for the precipitation of the type II and type III carbonate cements, causing enriched δ 18 O values of the pore fluids during the precipitation of the type II and type III carbonate cements. Although the earlier dissolved pores were filled with ferrocalcite, dolomite and ankerite in the middle–late diagenetic stages, some residual pores and fractures remained to become the potential reservoir storage spaces for the oil and gas exploration in the Jiyuan area.